ELECTRIC CONDUCTIVITY OF Fe2SiO4–Fe3O4 SPINEL SOLID SOLUTIONS - Yamanaka T.; Shimazu H.; Ota K. (My University, 2001)
The spinel solid solution was found to exist in the whole range between Fe3O4 and γ-Fe2SiO4 at over 10 GPa. The resistivity of Fe3− x Si x O4 (0.0<x<0.288) was measured in the temperature range of 80∼300 K by the AC impedance method. Electron hopping between Fe3+ and Fe2+ in the octahedral site of iron-rich phases gives a large electric conductivity at room temperature. The activation energy of the electron hopping becomes larger with increasing γ-Fe2SiO4 component. A nonlinear change in electric conductivity is not simply caused by the statistical probability of Fe3+–Fe2+ electron hopping with increasing the total Si content. This is probably because a large number of Si4+ ions occupies the octahedral site and the adjacent Fe2+ keeping the local electric neutrality around Si4+ makes a cluster, which generates a local deformation by Si substitution. The temperature dependence of the conductivity of solid solutions indicates the Verwey transition temperature, which decreases from 124(±2)K at x=0 (Fe3O4) to 102(±5)K at x=0.288, and the electric conductivity gap at the transition temperature decreases with Si4+ substitution.
Keywords: FE3-x SIx O4 SPINEL SOLID SOLUTION; SOLID SOLUTION; CATION DISTRIBUTION; ELECTRIC CONDUCTIVITY; VERWEY TRANSITION TEMPERATURE; NONSTOICHIOMETRY